Palatability of shrubs and fodder trees measured on sheep and camels. Methodological approach and preliminary results - Ben Salem H.; Nefzaoui A.; Abdouli H. (Fodder trees and shrubs, 1994)
Experiments were performed to study the effect of measurement duration on palatability of eleven range species and to define thereafter a palatability index. The range species were randomly distributed in five combinations (C1 to C5) containing each four species. Each combination was tested over a 15-day experimental period on four one-year old sheep and five two-year old one-humped camels (camelus dromedarius). Animals received daily at 0800h the four range species ad libitum and were supplemented at 1700h with spineless cactus. The barley hay (standard food) was distributed with the range species only during the first five days of each experimental period. Food intakes measured on the first day (l1), average food intakes on the first five-day period (l5), the second five-day period (l10) and the third five-day period (l15) were compared. Significant correlations (P less than 0.05) were found between l1 and l5 (r
ECC-CAMAR 800-CT90-0021 Research Project Meeting on Fodder Trees and Shrubs, 1992/10/12-13, Palermo (Italy)